2014
DOI: 10.1186/gb-2014-15-3-r47
|View full text |Cite
|
Sign up to set email alerts
|

Clinical drug response can be predicted using baseline gene expression levels and in vitro drug sensitivity in cell lines

Abstract: We demonstrate a method for the prediction of chemotherapeutic response in patients using only before-treatment baseline tumor gene expression data. First, we fitted models for whole-genome gene expression against drug sensitivity in a large panel of cell lines, using a method that allows every gene to influence the prediction. Following data homogenization and filtering, these models were applied to baseline expression levels from primary tumor biopsies, yielding an in vivo drug sensitivity prediction. We val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
708
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 732 publications
(712 citation statements)
references
References 53 publications
3
708
1
Order By: Relevance
“…This information can be used to systematically train computational models of the molecular signaling pathways contributing to drug sensitivity and resistance in various cancer settings, and to propose novel drug targets and combination approaches. Cell line screens have provided some success in explaining or predicting drug responses by driver gene mutations (2)(3)(4); however, in many cases the true mechanism of resistance remains elusive or more complex. Most predictive methods routinely used today use correlative statistics or feature-based learning techniques such as machine learning, while network methods remain scarce despite their potential for extracting mechanistic insights and actionable biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…This information can be used to systematically train computational models of the molecular signaling pathways contributing to drug sensitivity and resistance in various cancer settings, and to propose novel drug targets and combination approaches. Cell line screens have provided some success in explaining or predicting drug responses by driver gene mutations (2)(3)(4); however, in many cases the true mechanism of resistance remains elusive or more complex. Most predictive methods routinely used today use correlative statistics or feature-based learning techniques such as machine learning, while network methods remain scarce despite their potential for extracting mechanistic insights and actionable biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Ridge regression has been used in [57] to predict chemotherapeutic response in patients using only before-treatment baseline tumor gene expression data. The authors compared the performance with other approaches like random forests [58], nearest shrunken centroids [59], principal component regression [60,61], LASSO [42] and elastic net [44] regression and observed that ridge regression was the best performer.…”
Section: Linear Regression Modelsmentioning
confidence: 99%
“…As mentioned earlier, both the drug type that is being predicted or the different molecular features being used to design the predictive model can play a significant role. For instance, in the study [57], they used chemotherapeutic, whereas [25] used primarily targeted drugs. Furthermore, [57] used gene expression data alone, whereas [25] used multiple types of genomic data, including gene expression, RNA-Seq, RPPA, methylation, CNV and SNP.…”
Section: Linear Regression Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geeleher et al . (2014) fitted a ridge regression model of whole‐genome gene expression in cell lines against in vitro drug half maximal inhibitory concentration (IC 50 ) values and then used the model with tumor expression data from a clinical trial to estimate drug response. Chang et al .…”
Section: Introductionmentioning
confidence: 99%